2002
DOI: 10.1021/om020421k
|View full text |Cite
|
Sign up to set email alerts
|

HRh(dppb)2, a Powerful Hydride Donor

Abstract: The Rh(I) and Rh(III) hydrides HRh(dppb)2 and [HRh(dppb)2(NCCH3)](BF4)2 (where dppb is 1,2-(bis(diphenylphosphino)benzene) have been prepared, and a structural study of [HRh(dppb)2(NCCH3)](BF4)2 has been completed. The latter complex is an octahedral complex with a trans arrangement of the hydride and acetonitrile ligands. A pK a value of 9.4 was measured for this complex by equilibration of [Rh(dppb)2](BF4) with 4-bromoanilinium tetrafluoroborate in acetonitrile. [Rh(dppb)2](BF4) reacts with H2 in the presenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
92
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(102 citation statements)
references
References 36 publications
10
92
0
Order By: Relevance
“…The synthesis of bischelate complexes B has previously been reported for several ligands, 27 including ligand 4a. 28 James and co-workers showed that structure B containing either 1,2-bis(diphenylphosphino)ethane or 1,3-bis(diphenylphosphino)propane ligands is quantitatively converted to dimer C under hydroformylation conditions, presumably via compound A. 29 Also for ligand 4a, we observed the slow conversion of B to dimer C in the highpressure NMR experiments.…”
Section: Dsupporting
confidence: 49%
“…The synthesis of bischelate complexes B has previously been reported for several ligands, 27 including ligand 4a. 28 James and co-workers showed that structure B containing either 1,2-bis(diphenylphosphino)ethane or 1,3-bis(diphenylphosphino)propane ligands is quantitatively converted to dimer C under hydroformylation conditions, presumably via compound A. 29 Also for ligand 4a, we observed the slow conversion of B to dimer C in the highpressure NMR experiments.…”
Section: Dsupporting
confidence: 49%
“…DuBois and coworkers (11)(12)(13)(14) investigated the thermodynamic hydride-donor abilities (i.e., hydricities) of transition-metal hydrides, formyl complexes, and NADPH-model complexes, such as 1-benzyl-1,4-dihydronicotinamide, in order to develop CO 2 -reduction catalysts in CH 3 CN. The thermodynamic hydricity of a species AH − (or BH) is defined as the standard free energy change for the reaction:…”
Section: Modelmentioning
confidence: 99%
“…The stability in solution decreases in the order 1'' > 1' > 1, and the lifetime depends on the temperature and solvent: typically, at 300 K in CH 2 Cl 2 it is a few hours for 1'' and roughly one hour for 1. Therefore, [PdH(dppe) 2 ] + BF 4 À was further characterized by 13 C and 19 F NMR spectroscopy at low temperature, as in the time needed for the recording the spectrum no decomposition took place. Conversely, 1 and 1' under the same conditions start to decompose, so that it is not possible to obtain a clean spectrum, and signal assignment is difficult.…”
Section: Resultsmentioning
confidence: 99%